Validation of the Turkish version of the Chronic Stress Scale: assessing social role-related stressors and their impact on psychopathology - Yapici Eser, Hale; Ertuna, Defne; Yalcinay-Inan, Merve; Kurt Sabitay, Imren; Balli, Muhammed; Kilciksiz, Can Misel; Kucuker, Mehmet Utku; Kilic, Ozge; Ercan, A. Cenk; Guclu, Oya; Aydemir, Ömer (Frontiers in Psychology, 2024)
Chronic social-role related stress plays a crucial role in the development and progression of mental and medical disorders, making it an important factor to consider. This study aimed to translate and validate The Chronic Stress Scale (CSS) by Turner et al. (1995), for a Turkish population and explore its role in depression, anxiety and perceived stress.Methods: A total of 524 participants (mean age 31.59 years, 68% women) were recruited from Koç University and Basaksehir Cam Sakura City Hospitals, including 260 from the general population and 264 with depressive or anxiety disorders. The 51-item CSS was translated into Turkish and validated through reliability and validity analyses, including Cronbach's alpha, exploratory factor analysis, and correlations with the Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), and Perceived Stress Scale (PSS-14).The Turkish CSS showed good internal consistency (Cronbach's alpha = 0.90) and identified 13 dimensions of chronic stress (Partner, children, work, loneliness, financial, workload, debt, relationship inoccupancy, family health, residence, family, ex-partner, and others). Dimensions were named based on the content of the items included. Significant correlations were found between CSS and BDI (r = 0.611, p < 0.001), BAI (r = 0.558, p < 0.001), and PSS-14 (r = 0.222, p < 0.001). Discriminant validity revealed significant score differences between clinical and general populations.The Turkish CSS is a reliable and valid tool for assessing chronic social role-related stressors, supporting its use for both research and practice.